Quality of life and empowerment among women - Purnima Kundu; Linu Sara George; Renjulal Yesodharan (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: Few women in history were respected by society because of their contributions to the field of science, arts, politics, and so on, but in general, women are deprived of their rights and being refrained from decision-making in major areas of individual and family life. This research tried to investigate the degree of empowerment and quality of life (QOL) of the women to find out the relationship between empowerment and QOL of women. MATERIALS AND METHODS: An exploratory survey was carried out among 210 purposively selected married women aged between 20 and 49 years in a selected municipality area of West Bengal. Data were obtained by one-to-one interviews using Women Empowerment Interview Schedule and WHOQOL Scale BREF. RESULTS: The mean total QOL score of the women was found as 98.59 ± 13.61. The transformed scores in the physical, psychological, social relation, and environmental domains were 74.92 ± 14.97, 66.58 ± 15.78, 81.00 ± 18.07, and 65.28 ± 17.99, respectively. The degree of empowerment was calculated as 64.71 ± 6.79. Among the women, 5% had poor, 62% had medium, and 33% had a high degree of empowerment. A weak positive correlation (r = 0.325, P = 0.001) was found between QOL and empowerment. Significant associations were established between empowerment and education (Fisher's exact = 13.975 [0.007]) and education gap with husband (Fisher's Exact = 8.68, P 0.069). Multiple regression analysis between empowerment dimensions and QOL shows that personal or family dimensions, including health, are a significant predictor for the QOL (P < 0.01). CONCLUSION: Most of the women had medium degree of empowerment. Increased degree of empowerment improves their QOL of women. Women should be aware of their rights that can enhance the empowerment in different dimensions of life.